Money and financial intermediation : the theory and structure of financial systems - Smith, Paul F. (Englewood Cliffs, N.J. : Prentice-Hall, 1978)
The book is designed to integrate the many new developments in the theory of financial decisions and behavior into the story of the financial process in its role in supporting and shaping economic activity. It views money as part of a system of monetary aggregates that play a complex role in determining the level of interest rates and economic activity. It views banks as one of a set of financial institutions that convert savings into usable loan funds. The emphasis of the book is on the structure and organization of the private financial system as it has developed to supply these needs. The book assumes that the reader is familiar with elementary economics and statistics. The book is subdivided into two main parts: the first deals with the microeconomics of finance, the second with the macroeconomics of finance.
Includes bibliographies and index.
rpm 24/04/2018
Loans
Keywords: Financial institutions; Money; Intermediation (Finance); Financial systems